A method proposal to support decision-making in unstable ecosystems: application in the Brazilian eSports ecosystem case. (18th June 2020) - Ikenami, Rodrigo Kazuo; Lipovaya, Viktoriya; Costa, Patrícia Gomes Ferreira Da; Silva, Édison Renato; Martins, Paula Salomão; Lobo, Luiza Da Silveira; Duarte, Francisco José
This study investigated the term 'ecosystem' and its contribution to the strategic management field. This feature fits in with the business scenario, surrounded by uncertainties and risks. The role of the leader/orchestrator is particularly important to navigate under these circumstances. Additionally, the maturity stage mindset helps to locate the ecosystem's conditions and trends. In order to apply these principles into a practical framework, an investigation was made focusing on ecosystem boundaries. An ecosystem starts from the end user value proposition offer and it should integrate the suppliers and complementors where there is instability in the delivery flow. We argue that the leader/orchestrator moves should align with the ecosystem's maturity stage orientations. A method was tested in the eSports ecosystem and the results confirmed most of our assumptions and propositions.